The Relationship Between People’s Environmental Considerations and Pro-environmental Behavior in Lithuania - Balundė, Audra; Perlaviciute, Goda; Steg, Linda (Frontiers in Psychology, 2019)
Given the need for global action on climate change, it is crucial to comprehend which factors motivate people in different countries to act more pro-environmentally. Lithuania is a post-socialist country that has recently increased commitment to foster pro-environmental behavior of individuals, by implementing interventions that target mainly the personal costs and benefits of relevant behaviors. Yet, research suggests that people’s general environmental considerations, namely biospheric values and environmental self-identity, can drive people’ pro-environmental behavior and may be important targets for interventions. These studies, however, have been mostly conducted in Western Europe and the US, with limited evidence of relationship between people’s biospheric values, environmental self-identity and pro-environmental behaviors across different countries and cultures. We performed a correlational study with a convenience sample in Lithuania (n=334). Consistent with previous studies and the theory, our study revealed that people’s general environmental considerations were positively related with recycling and environmental activism, but not with fuel-efficient driving and the use of sustainable transportation in Lithuania. We conclude that general environmental considerations are related to pro-environmental behaviors beyond Western Europe and the US. Yet, future studies need to examine the boundary conditions of this relationship and test whether interventions targeting environmental consideration can be effective to promote pro-environmental behavior.